Pendekatan Saintifik dalam Pendidikan Islam Menyongsong Era Revolusi 4.0 - Sabri, Ahmad (Turast: Jurnal Penelitian dan Pengabdian, 2020)
This study aims to describe how a scientific approach in Islamic education in the 4.0 revolution era. This study is important because the era of the industrial revolution 4.0 is a phenomenon that collaborates with cyber technology and automation technology. The concept of the application is centered on the concept of automation by technology without using human labor in the application process. The essence of the 4.0 revolution demands the need for educative efforts to improve the quality of qualified and multicompetent human resources. For this reason, the implementation of a scientific approach to learning is an appropriate alternative. Regarding the scientific approach, Islamic education also has its own perspectives and strategies in facing the revolution era 4.0. Islamic education sourced from the Koran and Hadith always encourages the importance of learning through observation, asking, trying, processing, presenting, reasoning and creating in order to give birth to the quality of competitive human resources based on the values of faith and piety to Allah SWT. From the perspective of Islamic education, the implementation of a scientific approach that does not reduce the values of faith and piety will give birth to an optimistic quality of human resources and will always struggle to face every change by optimizing every potential it has. Thus, unwittingly the 4.0 revolution era will have an impact on the number of people losing their jobs and the quantity of unemployment will continue to increase given a large number of jobs that have been mechanically replaced by mechanical power.